Cellulose Depolymerization with LPMO‐inspired Cu Complexes. Issue 22 (22nd September 2021) - Castillo, Ivan; Torres‐Flores, Andrea P.; Abad‐Aguilar, Diego F.; Berlanga‐Vázquez, Armando; Orio, Maylis; Martínez‐Otero, Diego
Abstract: Bis(benzimidazole)amine‐based copper complexes, with structural similarities to the active sites of Lytic Polysaccharide Monooxygenase enzymes (LPMOs), were tested for the oxidative degradation of cellulose. Spectroscopic characterization of the complexes, as well as structural authentication of one of them, confirm a tetragonal coordination environment with 3 nitrogen donors, as well as a thioether in axial positions. Aqueous oxidative degradation of cellulose was achieved with the Cu II complexes and H2 O2 as oxidant through putative cupric‐hydroperoxo intermediates. Conversion of cellulose was achieved in up to 67 % yield of soluble oligosaccharide derivatives at ambient temperature and pressure. The products were analyzed in aqueous solution by HPLC‐MS, confirming oxidative depolymerization of cellulose under ambient conditions, in an analogous fashion to LPMOs. Abstract : Biomimetic chemistry : LPMO‐inspired benzimidazole‐based copper complexes oxidatively degrade cellulose to cellobiose, aldonic acid and levoglucosan as soluble products in the presence of hydrogen peroxide/triethylamine as oxidant mixture under mild conditions through initially formed cupric hydroperoxo intermediates.